1999
DOI: 10.1152/ajpendo.1999.277.1.e49
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of salmon calcitonin on secretion of progesterone and GnRH-stimulated pituitary luteinizing hormone

Abstract: The effects of salmon calcitonin (sCT) on the production of progesterone and secretion of luteinizing hormone (LH) were examined in female rats. Diestrous rats were intravenously injected with saline, sCT, human chorionic gonadotropin (hCG), or hCG plus sCT. Ovariectomized (Ovx) rats were injected with saline or sCT. In the in vitro experiments, granulosa cells and anterior pituitary glands (APs) were incubated with the tested drugs. Plasma LH levels of Ovx rats were reduced by sCT injection. Administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Binding of CT with membrane receptors was found to be saturable with high affinity (Bmax, 1.2 pmol/mg protein, Kd 48.8 pmol/L). Available information on the presence of CT-binding sites and sCT-induced inhibition of progesterone secretion in rat granulosa cells indicates a physiological role of CT at ovarian levels in mammals (Tsai et al, 1999). Our finding is the first report of the presence of sCT receptor in fish ovary apart from its presence in gills.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Binding of CT with membrane receptors was found to be saturable with high affinity (Bmax, 1.2 pmol/mg protein, Kd 48.8 pmol/L). Available information on the presence of CT-binding sites and sCT-induced inhibition of progesterone secretion in rat granulosa cells indicates a physiological role of CT at ovarian levels in mammals (Tsai et al, 1999). Our finding is the first report of the presence of sCT receptor in fish ovary apart from its presence in gills.…”
Section: Discussionsupporting
confidence: 55%
“…Wang et al, (1994) found that www.intechopen.com CT-like peptides, human CT, salmon CT and CT-gene related peptide inhibit spontaneous and gonadotropin-stimulated testosterone secretion by acing directly on testes and also by reducing the release of pituitary luteinizing hormone (LH). Inhibition of salmon CT on secretion of progesterone-and gonadatropin-releasing hormone (GnRH)-stimulated release of pituitary LH in rat also has been documented (Tsai et al, 1999). Very recently, we also reported for stimulation of salmon CT on secretion of 17β-estradiol by the ovarian follicles of common carp C. carpio (Paul et al, 2008).…”
Section: Other Function Of Ct In Vertebratesmentioning
confidence: 67%
“…The preparation of granulosa cells was modified from the method described elsewhere. 20,21 The immature female rats (22-25 days of age) were injected subcutaneously with PMSG (15 IU/rat). After 48 h, rats were killed by cervical dislocation.…”
Section: Preparation Of Granulosa Cells For Cell Culturementioning
confidence: 99%
“…The preparation of granulosa cells was modi®ed from the method described elsewhere (Hwang et al, 1996;Tsai et al, 1999). The immature female rats 22 ± 25 days of age were injected subcutaneously with PMSG (15 iu rat…”
Section: Isolation and Culture Of Granulosa Cellsmentioning
confidence: 99%